Odpowiedź :
[tex]2z - y = 2 \times 3 - 4 = \\ 6 - 4 = 2[/tex]
[tex]5x + 2y + z = \\ 5 \times ( - 1) + 2 \times 4 + 3 = \\ - 5 + 8 + 3 = 6[/tex]
[tex]2xz + y = \\ 2 \times ( - 1) \times 3 + 4 = \\ 6 + 4 = 10[/tex]
[tex]x + z = \\ ( - 1) + 3 = 2[/tex]
[tex]2y + 6x = \\ 2 \times 4 + 6 \times ( - 1) = \\ 8 + 6 = 14[/tex]
[tex]yz + 10x = \\ 4 \times 3 + 10 \times ( - 1) = \\ 12 + 10 = 22[/tex]
[tex](z - x) \div 2 = \\ (3 - ( - 1)) \div 2 = \\ (3 + 1) \div 2 = \\4 \div 2 = 2[/tex]
[tex]3z - 2y + x = \\ 3 \times 3 - 2 \times 4 + ( - 1) = \\ 9 - 8 + ( - 1) = \\ 0[/tex]
[tex]xyz + 10 = \\ ( - 1) \times 4 \times 3 + 10 = \\ 12 + 10 = 22[/tex]
[tex]y - z + x = \\ 4 - 3 + ( - 1) = 0[/tex]
[tex]12 - 5z - x = \\ 12 - 5 \times 3 - ( - 1) = \\ 12 - 15 + 1 = - 2[/tex]
Proszę bardzo ☺️